ANALYSIS OF THE FULFILLMENT OF POLITICAL PARTICIPATION RIGHTS FOR PEOPLE WITH DISABILITIES IN THE PROCESS OF ELECTIONS IN INDONESIA - Nanda Yuniza Eviani; Wanda Anggraeni; Putri Patresia Ahmad (Cahaya Ilmu Bangsa, 2024)
The objective of this study is to identify the obstacles that impede the realization of political participation rights for individuals with disabilities during the electoral process in Indonesia, as well as potential solutions to these challenges. The normative and doctrinal research methods were utilized in this study. The materials were gathered through the utilization of both literature and field investigation. This research identifies at least three significant obstacles to the implementation of political participation rights for individuals with disabilities. Enforcement of laws and regulations and sociocultural factors are the issues. Potential remedies for these challenges include augmenting the enforcement of laws and regulations, as well as implementing social programs that benefit both the government and the community.